2022
DOI: 10.1111/cas.15665
|View full text |Cite
|
Sign up to set email alerts
|

Influences of intratumoral heterogeneity on assessment of tumor microenvironment in esophageal squamous cell carcinoma

Abstract: The intratumoral heterogeneity (ITH) of the tumor microenvironment (TME) has yet to be addressed in esophageal squamous cell carcinoma (ESCC). Here, we studied the ITH of CD8 and PD‐L1 status in ESCC, and examined the potential of the tumor surface for representing the TME. In total, 67 surgically resected clinical Stage II ESCC specimens were analyzed. The CD8‐cell density, PD‐L1 tumor proportion score (TPS), and combined positive score (CPS) were calculated in three (superficial, middle, and deep) areas of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…16,18 In accordance with previous investigations, we herein showed the combination of T cells and PD-L1 status to be useful for stratifying survival outcomes. 10,12,27 No survival impact of CD8 + was detected in our cohort. A recent study underscored the significance of CD8 + status in ESCC patients, 18 although other studies have suggested modest survival impacts of CD8 + cells alone, especially in NAC-treated tumors.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…16,18 In accordance with previous investigations, we herein showed the combination of T cells and PD-L1 status to be useful for stratifying survival outcomes. 10,12,27 No survival impact of CD8 + was detected in our cohort. A recent study underscored the significance of CD8 + status in ESCC patients, 18 although other studies have suggested modest survival impacts of CD8 + cells alone, especially in NAC-treated tumors.…”
Section: Discussionmentioning
confidence: 60%
“…46 A precise evaluation methodology for TME remains to be established in various specific malignancies, including ESCC. 19 Although we recently suggested that tumor surface information might reasonably be used for predicting the immune status of the whole tumor in ESCC, 27 TME evaluation of small tumors, such as early stage resections or biopsy samples, are easily affected by ITH. We evaluated only primary tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations